Validation of a serum neutralization test for detection of antibodies specific to cyprinid herpesvirus 3 in infected common and koi carp (Cyprinus carpio). Issue 5 (22nd September 2016) - Cabon, J; Louboutin, L; Castric, J; Bergmann, S; Bovo, G; Matras, M; Haenen, O; Olesen, N J; Morin, T
Abstract: Cyprinid herpesvirus 3 (CyHV‐3) is the aetiological agent of a serious infective, notifiable disease affecting common carp and varieties. In survivors, infection is generally characterized by a subclinical latency phase with restricted viral replication. The CyHV‐3 genome is difficult to detect in such carrier fish that represent a potential source of dissemination if viral reactivation occurs. In this study, the analytical and diagnostic performance of an alternative serum neutralization (SN) method based on the detection of CyHV‐3‐specific antibodies was assessed using 151 serum or plasma samples from healthy and naturally or experimentally CyHV‐3‐infected carp. French CyHV‐3 isolate 07/108b was neutralized efficiently by sera from carp infected with European, American and Taiwanese CyHV‐3 isolates, but no neutralization was observed using sera specific to other aquatic herpesviruses. Diagnostic sensitivity, diagnostic specificity and repeatability of 95.9%, 99.0% and 99.3%, respectively, were obtained, as well as a compliance rate of 89.9% in reproducibility testing. Neutralizing antibodies were steadily detected in infected carp subjected to restrictive or permissive temperature variations over more than 25 months post‐infection. The results suggest that this non‐lethal diagnostic test could be used in the future to improve the epidemiological surveillance and control of CyHV‐3 disease.